Global Migration Revisited : Short-Term Pains, Long-Term Gains, and the Potential of South-South Migration - Ahmed, S. Amer; Go, Delfin S.; Willenbockel, Dirk (World Bank, Washington, DC, 2016)
This paper re-examines the development implications of international migration focusing on two issues: how the costs and benefits of migration change over time, and the significance of South-South migration for development. First, the analysis finds that although greater migration could push down the wages of native workers of advanced countries in the short run, these wages eventually recover. This pattern would be mostly caused by the beneficial effect of additional labor on the real returns on capital and fostering faster capital formation. Additional South-North migration could favor capital income recipients and reduces labor income in host regions in the short run. In contrast, in sending countries, capital owners could experience lower incomes while wages rise. Globally, the welfare gains of new migrants could be expected to exceed the losses of old migrants by a wide margin. The remaining natives in sending countries could enjoy a net increase in remittances as well as an increase in labor income, although income from capital might decline. Second, in a hypothetical scenario with lower South-South migration, the implied losses of remittance income could lead to substantially lower welfare in developing countries. Although the wage differentials among developing countries tend to be smaller relative to their wage differentials with high-income countries, South-South migrants make substantial contributions to remittances.